Mediterranean voyages : the archaeology of island colonisation and abandonment - Dawson, Helen (Publications of the Institute of Archaeology, University College London, 2014)
"Islands are ideal case studies for exploring social connectivity, episodes of colonisation, abandonment, and alternating phases of cultural interaction and isolation. Their societies display different attitudes toward the land and the sea, which in turn cast light on group identities. This volume advances theoretical discussions of island archaeology by offering a comparative study of the archaeology of colonisation, abandonment, and resettlement of the Mediterranean islands in prehistory. This comparative and thematic study encourages anthropological reflections on the archaeology of the islands, ultimately focusing on people rather than geographical units, and specifically on the relations between islanders, mainlanders, and the creation of islander identities. This volume has significance for scholars interested in Mediterranean archaeology, as well as those interested more broadly in colonisation and abandonment"--